Analysis of Pile Response to Excavation Induced Ground Movements - Nishanthan, R.; Liyanapathirana, D.S.; Leo, C.J. (University of Western Sydney, 2012)
This paper presents a parametric study for the pile response and ground movements due to deep excavations supported by stable retaining walls. The coupled behaviour of a single pile subjected to excavation induced ground movements is analysed using the finite element method, which has the ability to simulate construction sequences and various lateral earth retaining systems. The constitutive behaviour of the soil is modelled using the Mohr-Coulomb model. The pile is assumed to have the linear elastic behaviour. The numerical model was verified using centrifuge test data found in the literature and a parametric study is carried out to develop design charts to establish variation patterns among number of influence factors such as geometry of the excavation, soil properties, structural system variables, pile fixity conditions and pile location with respect to the excavation.